Restorative Justice in Drug User Rehabilitation: An Islamic Legal and Maqāṣid al-sharīʿah Analysis of the National Narcotics Agency in Jambi - Harianto Sitepu; Risnita Risnita; Hermanto Harun; Abdul Halim (International Journal of Sociology and Law, 2026)
Drug misuse continues to be a complicated social and legal issue that has an impact on societal stability, public health, and personal wellbeing. Many criminal justice systems have moved away from punitive tactics in favor of rehabilitation-focused ones in recent years, especially for drug users who are frequently viewed as sufferers of addiction rather than serious criminals. The National Narcotics Agency (BNN) in Indonesia is implementing rehabilitation programs and restorative justice processes as a result of this change. This study investigates the efficacy of restorative justice in drug rehabilitation at Jambi Province's National Narcotics Agency and evaluates its applicability from the standpoint of Islamic law, specifically the framework of maqāṣid al-sharīʿah. The study uses a case study design and a qualitative methodology. Participant observation, document analysis, and in-depth interviews with BNN officials, rehabilitation counselors, medical staff, and ex-drug users were used to gather data. The results show that an integrated evaluation system that assesses drug users' physical, psychological, and social states in order to determine their eligibility for recovery is used to institutionally apply restorative justice principles. Combining medical care, psychological counseling, and social reintegration programs, the rehabilitation programs greatly aid in participants' recuperation, enhance psychological stability, and fortify familial ties. Additionally, by promoting individual responsibility, family support, and community involvement, restorative justice-based rehabilitation lowers the risk of recidivism. From the standpoint of Islamic legal philosophy, these actions are consistent with the goals of maqāṣid al-sharīʿah, specifically the defense of human dignity, life (ḥifḍ al-nafs), and intellect (ḥifḍ al-ʿaql). According to the study's findings, restorative justice-based rehabilitation is a compassionate and successful method of treating drug dependency while encouraging social reintegration and long-term recovery.